Analisis Pengaruh Iklan, Harga dan Variasi Produk terhadap Keputusan Pembelian di Toko Rumah Mebel Pekanbaru - Astri Ayu Purwati; Josua Julius Siahaan; Zulfadli Hamzah (UIR Press, 2019)
The increasing needs of the community for furniture have an effect on industrial trade. For this reason, each store competes in increasing sales volume. With the increasing number of shops engaged in the same field, the competition in the business world will increase. The purpose of this study is to determine the effect of Advertising, Prices, and Product Variants on consumer satisfaction Pekanbaru Furniture Store. The population in this study is consumers who purchase products at the Pekanbaru Rumah shop. The number of samples in this study was 100 respondents who are customers of Pekanbaru Furniture House stores. The results of this study indicate that Product Prices and Variations affect consumer satisfaction in Pekanbaru Home stores and the results of the Advertising research do not affect consumer satisfaction in Rumah Mebel stores. Rumah Mebel Stores need to pay attention to the ads that are made, because this has no effect on the approach to consumers. The price set by the house is in accordance with the perspective and consumers get this price discount which makes the price influence the purchasing decision. And the variations of products made Rumah Mebel are as varied as the complete product size, type of product and product ingredients also influence purchasing decisions.